Credit constraints, firm investment and growth: Evidence from survey data - Miguel García-Posada Gómez (European Central Bank (ECB), 2018)
We assess the impact of credit constraints on investment, inventories and other working capital and firm growth with a large panel of small and medium-sized enterprises from 12 European countries for the period 2014-2016. The data come from the Survey on the access to finance of enterprises (SAFE), a survey that is especially designed to analyse the problems in the access to external finance of European SMEs. The key identification challenge is a potential reverse-causality bias, as firms with poor investment and growth opportunities may have a higher probability of being credit constrained. We implement several strategies to overcome this obstacle: proxies for investment opportunities, lagged regressors, random effects and instrumental variables. Our findings suggest that credit constraints, both in bank financing and other financing (e.g. trade credit), have strong negative effects on investment in fixed assets, while the impact on firm growth and working capital is less robust.
Keywords: G30; G31; G32; 330; investment; firm growth; working capital; ordered probit; instrumental variables